Creative Scenario Options For Regional Economy Development - Tursunalievich, Abdulxakimov Zuhrali; Rahmat, Abdul (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
This article explores ways to develop small areas within the regions of the Republic of Uzbekistan and develops scenario options for small areas.